2021
DOI: 10.22617/wps210096-2
|View full text |Cite
|
Sign up to set email alerts
|

Education and the Evolution of Comparative Advantage

Abstract: The paper provides the first evidence that countries with high education levels were more successful in developing comparative advantage in products unrelated to those they already export. In contrast, education appears unimportant for developing comparative advantage in products that are intrinsically complex or education intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In a study of low-and middle-income countries, Felipe et al (2021) found that those countries that had high education levels were more successful in developing comparative advantage in the products that are unrelated to those they already exported. This indicated the key role that education provides in shifting between products produced and facing the challenges that come with the change.…”
Section: 5mentioning
confidence: 99%
“…In a study of low-and middle-income countries, Felipe et al (2021) found that those countries that had high education levels were more successful in developing comparative advantage in the products that are unrelated to those they already exported. This indicated the key role that education provides in shifting between products produced and facing the challenges that come with the change.…”
Section: 5mentioning
confidence: 99%
“…Education enables countries to improve comparative advantage in new product categories. In fact, quality primary education has a strong correlation with countries' development of their comparative advantage in related products that they are already producing (Felipe et al 2021). It is also a core determinant for countries following an FDI-led growth strategy (Brooks et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparative advantage, driven by technology or factor analysis, is at the core of the neoclassical trade theory (Costinot, 2009). Countries with high education levels were more successful in developing a comparative advantage in products unrelated to those they had already exported (Felipe et al ., 2021). This theory is also applicable to the analysis of educational cooperation between cities.…”
Section: Introductionmentioning
confidence: 99%